2010 3rd International Conference on Information Management, Innovation Management and Industrial Engineering 2010
DOI: 10.1109/iciii.2010.337
|View full text |Cite
|
Sign up to set email alerts
|

Management Innovation of IT Project Managers

Abstract: Compared with other projects, information technology (IT) projects are unique, which are characterized by emergency, uniqueness, one shot, short term and uncertainty. To implement an IT project successfully, problems in the IT project management must be found, analyzed and solved and there must be successful project management and management innovation as well. Then, what are the major problems in IT project management? Who can conduct IT project management successfully? How to conduct IT project management su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The majority of project managers in the software and information technology (IT) sector have technical skills rather than managerial skills in different projects (Ko & Kirsch, 2017;Dobie, 2020). It has been reported that IT projects have failed because project managers have not been equipped with management skills (Liu & Liu, 2010;Lauesen, 2020) . Papke-Shields et al (2010) argued that the implementation of standard project management processes is essential for all organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of project managers in the software and information technology (IT) sector have technical skills rather than managerial skills in different projects (Ko & Kirsch, 2017;Dobie, 2020). It has been reported that IT projects have failed because project managers have not been equipped with management skills (Liu & Liu, 2010;Lauesen, 2020) . Papke-Shields et al (2010) argued that the implementation of standard project management processes is essential for all organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The Standish Group International, Inc. reported in 2001 that 31 percent of all information technology (IT) projects were cancelled before completion, that only 16 percent of projects were completed successfully, and that 88 percent of all projects were over budget, overschedule or both. Standish reported an average cost overrun of 189 percent and an average time overrun of 222 percent of original estimates [3].The project thereby isn't completed successfully creating chaos among the project members and the pressure is on the project manager to meet the deadline. To avoid this situation we are trying to develop a project management application for students which will be helpful for them to plan, collaborate, discuss their projects with the project members and the guide; also scheduling the projects and carrying out the tasks in a timely manner will help the guide analyze the productive work of the students.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of leadership and management qualities of project manager along with communication channels for managing projects had been explored by some researchers [39][40][41][42]. The importance of IQ, EQ, and MQ had also been studied.…”
Section: Effects Of Leadership and Management Qualities Of Project Mamentioning
confidence: 99%
“…Leadership abilities, communication and management abilities along with IQ, EQ, and MQ of the project manager have a huge impact on the projects [39][40][41][42]. Teaching of project management is not only about just teaching of GANTT and PERT chart but also must include various software and other tools for successfully managing projects.…”
Section: -76mentioning
confidence: 99%